Students’ Attitudes Toward The Transformation of Online to Offline Learning in EFL Classroom - Lailatul Fatmawati; Daniar Sofeny; Syifa Khuriyatuz Zahro (Universitas Muhammadiyah Mataram, 2021)
Covid-19 pandemic enforced all educational institutions to adjust the learning environments from offline to online and from online to offline. The study aimed to find out the students’ attitude toward the transformation of online to offline learning in the EFL classroom. This descriptive quantitative study is a survey engaging in three Iyer attitude scales categories; enjoyment, academic efficacy, and anxiety as the instrument. From a total of 225 students in the tenth as the population, 39 students were responded the questionnaires as the sample through purposive sampling. The data obtained was later calculated for each responses’ percentage. The participation level of each three scales categories for both online and offline learning was interpreted using the interval scale modified from Erarslan and Topkaya. The interpretation result generated that the students enjoyed offline learning more than online learning, the students' academic efficacy was higher in online learning than offline learning, and the students' anxiety level in online learning is higher than offline learning. This result designates substantial insight for future policymaking by the government regarding the implementation of online and offline learning. Since it demonstrated that students enjoyed more offline learning. However, their academic efficacy and anxiety were higher in online learning.